Corporate ownership and the theory of the multinational enterprise. Issue 6 (December 2018) - Strange, Roger
Highlights: Traditional theories of the MNE need to be extended to embrace consideration of corporate ownership. Corporate ownership may involve different shareholder constituencies (e.g. State, family, institutions). Each shareholder constituency is likely to have different objectives, attitudes towards risk, and decision-making time horizons. Choices between (asset-exploiting and asset-augmenting) FDI and alternative strategies will depend in part upon corporate ownership. Abstract: This paper makes a contribution to the theory of the multinational enterprise (MNE) and, in particular, to why firms undertake foreign direct investment (FDI) rather than alternative strategies. We argue that FDI and its strategic alternatives involve different patterns of costs and returns over time, and hence different levels of risk and uncertainty. Traditional theories of the MNE conceptualize the firm as a risk-neutral decision-making entity with short-term efficiency objectives, and hence do not take these issues into account. This may be reasonable for firms with passive professional managers and widely-dispersed shareholders, operating in countries with the Anglo-American system of corporate governance. But many firms operate under quite different systems of corporate governance where concentrated shareholdings are commonplace and markets for corporate control are weak or non-existent. In these cases, shareholders exert considerable influence on all aspects of firm strategy including FDI. Furthermore, different groups of shareholders (State, family, institutions) are likely to have different objectives, different attitudes towards risk, and different decision-making time horizons. We thus suggest that the traditional theories of the MNE need to be extended to embrace consideration of corporate ownership (and other governance dimensions).